Proceedings of the 2018 International Workshop on Bioinformatics, Biochemistry, Biomedical Sciences (BBBS 2018) 2018
DOI: 10.2991/bbbs-18.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Variation on Photosynthetic Performance in Kiwifruit Seedling During Drought Stress and Rewatering

Abstract: Abstract. Drought stress adversely impact on the global crop growth and productivity. It is especially important to elucidate the physiological characteristics on plants under drought stress. With the prolongation of drought time, chlorophyll content continued to decline. Root activity increased significantly in mild and moderate drought periods, rapid decline in severe drought period; leaf net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs) and photochemical efficiency (ФPSⅡ) decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In another study, Zhang et al [ 32 ] also demonstrated that the root activity of A. chinensis cv. ‘Hongyang’ increased significantly in mild and moderate drought periods and rapidly declined in severe drought periods; the leaf net photosynthetic rate, transpiration rate, stomatal conductance and photochemical efficiency decreased significantly with increasing drought, while the intercellular CO 2 concentration increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhang et al [ 32 ] also demonstrated that the root activity of A. chinensis cv. ‘Hongyang’ increased significantly in mild and moderate drought periods and rapidly declined in severe drought periods; the leaf net photosynthetic rate, transpiration rate, stomatal conductance and photochemical efficiency decreased significantly with increasing drought, while the intercellular CO 2 concentration increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…This is why RDI has been mostly employed in fruit crops whose economic value is not determined by fresh weight, such as wine grapes [3], almonds [5], and prunes [6], among others. Furthermore, the fact that fresh-fruit growers have been hesitant to use this irrigation technique [7] is a good example of how the adoption of water conservative irrigation strategies, is strongly hindered by farmer's aversion to risk [8]. The implementation of successful RDI in fruit orchards must include several key points that are not always properly considered.…”
Section: Opinionmentioning
confidence: 99%
“…Chev.) may exhibit very high stomatal conductance [8], which explains the high vulnerability of kiwifruit to cavitation. On the other hand, leaves from highbush blueberry plants (Vaccinium corymbosum L.) have been reported to show an exponential reduction in stomatal conductance as water stress severity increases [9].…”
Section: Opinionmentioning
confidence: 99%